A multimodal analysis of the picturebook Daddy, Papa, and Me (2009). Deconstructing representational, interpersonal and compositional meanings - Martínez Lirola, María (Complutense Journal of English Studies, 2022)
This article offers a multimodal discourse analysis of the picturebook Daddy, Papa, and Me (2009), in which there is a two-father family with a child. The aim of this article is to analyse how the written text and the visual create meaning and to observe if the child has a symmetrical relationship with both fathers. We will follow the method of Visual Social Semiotics developed by Kress and van Leeuwen (2006) based on Halliday’s Systemic Functional Linguistics, in order to explore the representational, interpersonal and compositional meanings. The analysis will show that the child and his fathers are dynamic, as the actions represented in the visuals and the use of materials makes clear. However, the multimodal analysis does not encourage interaction with the readers, because most of the visuals are offers and the predominance of oblique angles. Images and written text are intergrated in the layout, but visuals are salient so that children can understand the meaning of the picturebook just looking at the images. The writer and the illustrator collaborate to tell the story in a simple way, with the aim of making the plot accessible to children and to invite them to identify with the actions being narrated.